2016
DOI: 10.22159/ijpps.2016v8i12.15141
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Activity of Novel Cur-Ca-Thione and Its Oxidative Stress Study

Abstract: Objective: Alzheimer's disease a progressive neurodegenerative disorder affected by the formation of amyloid beta and tau proteins. Medicinal plants have been proved significantly for its anti-oxidant and anti-inflammatory activity that might help in treating neurological disorders. Curcumin has been hugely studied in the treatment of various ailments but its water solubility and bioavailability is still a concern but we have tried to exterminate the problem by our formulation CUR-CA-THIONE. Now, we have expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Nevertheless, modification of curcumin by conjugating it with a carrier, encapsulation within the nanoparticle, and modification of its chemical structure have rendered positive results, including enhanced activity towards cancer cells, better wound healing properties, and strong antibacterial effects against Pseudomonas aeruginosa and Staphylococcus aures [ 89 , 90 ]. Shelat et al [ 91 ] reported that treatment with oral CUR-CA-THIONE, an alternative formulation derived from curcumin using glutathione and casein as vectors for better water solubility and brain bioavailability [ 89 ], at a dose of 500 mg/kg BW/day for 15 days to the aluminum chloride (AlCl 3 )-induced AD Wistar rats successfully inhibited LPO formation as measured by a thiobarbituric acid reactive substances (TBARS) assay ( p < 0.05) compared to untreated AD rats, which was associated with improved locomotor and exploratory behavior. Moreover, in an in vitro study, a curcumin derivative, demethoxycurcumin, reduced intracellular ROS generation induced by neurotoxic rotenone [ 92 ].…”
Section: Free Radicals and Oxidative Damage To Biomoleculesmentioning
confidence: 99%
“…Nevertheless, modification of curcumin by conjugating it with a carrier, encapsulation within the nanoparticle, and modification of its chemical structure have rendered positive results, including enhanced activity towards cancer cells, better wound healing properties, and strong antibacterial effects against Pseudomonas aeruginosa and Staphylococcus aures [ 89 , 90 ]. Shelat et al [ 91 ] reported that treatment with oral CUR-CA-THIONE, an alternative formulation derived from curcumin using glutathione and casein as vectors for better water solubility and brain bioavailability [ 89 ], at a dose of 500 mg/kg BW/day for 15 days to the aluminum chloride (AlCl 3 )-induced AD Wistar rats successfully inhibited LPO formation as measured by a thiobarbituric acid reactive substances (TBARS) assay ( p < 0.05) compared to untreated AD rats, which was associated with improved locomotor and exploratory behavior. Moreover, in an in vitro study, a curcumin derivative, demethoxycurcumin, reduced intracellular ROS generation induced by neurotoxic rotenone [ 92 ].…”
Section: Free Radicals and Oxidative Damage To Biomoleculesmentioning
confidence: 99%
“…In the contest of the use of this test, it might be emphasized that there are also other modifications and protocols including a working memory version, cognitive flexibility, neuroprotection, cholinergic dysfunction, and path integration in the MWM [11][12][13][14][15][16]. Testing the working memory in MWM is required due to information processing and working memory deficits in many central nervous system disorders, such as Schizophrenia, Parkinson, and Alzheimer's [17].…”
Section: Delayed Matching To Place Versionmentioning
confidence: 99%